Reaksi Pasar Modal Indonesia Terhadap Rencana Investasi Antara Pemerintah Indonesia dengan Pendiri Tesla dan Space X - Dewi, Ni Putu Ary Puspita; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi, 2023)
The high or low return received from an investment will be proportional to the risk borne. Investors can reduce this risk by analyzing the factors that cause risk from information that makes the capital market react. This research aims to determine the reaction of the Indonesian capital market to investment plans between the Indonesian government and the founders of Tesla and SpaceX by calculating abnormal returns and trading volume activity of metal and mineral industrial companies listed on the Indonesian Stock Exchange. This research uses the event study method. The observation period was carried out for 7 working days. The sampling method used was non-probability sampling with purposive sampling technique. The research results show that there are no significant abnormal returns on investment plan announcements, but the test results on trading volume activity show significant results. Keywords: Event Study; Abnormal Return; Trading Volume Activity